Analisa Perbandingan Proses Algoritma Elias Gamma Code dengan algoritma Elias Delta Code Dalam Kompresi File Audio Video Interleave - Pengalaman ndruru (PT. Ndruru Jaya Mandiri, 2025)
Abstract− Data compression is a method in computer science for reducing data size or compressing data. The data to be compressed is smaller in size than the previous data with the aim of saving storage. If data compression is carried out, the storage space required is small. Apart from being more efficient, compression can also result in faster data measurement times. As technology develops nowadays, data has a very important role, the large amount of data stored on memory or hard disk will result in a large increase in the used capacity of the storage media. There are two techniques that can be used to compress data, namely lossy compression and lossless compression. Lossy Compression is data file compression where the decompression results of the compressed data are not the same as the original data because there is information lost, but it can still be tolerated by eye perception. Lossy data compression will be effective when applied to images, films and digital sound. Meanwhile, Lossless compression is data compression where the decompression results of the compressed data are the same as the original data and no information is lost. One of the compression algorithms that can be used is the Elias Delta Code Algorithm which is a compression algorithm created by Peter Elias. The Elias Gamma Code code adds the length of the code in unary (α). The next code, δ(delta), is then added to the binary code (β). Elias Delta Code for positive integers, a bit more complex to construct. This algorithm can also compress large files to reduce the size of the file.